Warfarin Related Kidney Damage: A Confusing Case of Thrombophlebitis Masquerading as Infection - Samuelson Brittanee; Decker Matthew; Scott Hannah; Garrison Gregory (SAGE Publishing, 2023)
Anticoagulant-related nephropathy (ARN) is a rare, newly recognized cause of acute kidney injury and significant but underdiagnosed complication of anticoagulation therapy. ARN occurs in patients taking oral anticoagulant therapy most often warfarin or a novel oral anticoagulant (NOAC). It is a potentially devastating disorder with serious renal consequences and increased all-cause mortality. Anticoagulant-related nephropathy presents as an acute kidney injury (AKI) in the setting of a supratherapeutic INR with profuse glomerular hemorrhage seen as renal tubules filled with red cells and red cell casts on renal biopsy. Being that millions of Americans are on warfarin, a thorough understanding and awareness of the clinical presentation, diagnosis, and therapeutic interventions are crucial to protecting the renal function, lowering all-cause mortality and optimizing treatment. Our goal is to provide education on a newly recognized form of AKI and significant but underdiagnosed complication of anticoagulation therapy.